Interaction Between Fiscal Policy and Economic Fluctuation: A Case Study for Jordan - Alqaralleh, Huthaifa; Al-Saraireh, Ahmad; Alamro, Hassan (International Review of Management and Marketing, 2018)
The present research aimed to examine the interaction between fiscal policy tools and economic fluctuations in Jordan. This investigation is done by assessing both Government Expense and Tax Revenue over a quarterly sample period from 1980 till Q1 2017. The Band-Pass filter is adapted to define the fluctuation variables and hence to distinguish between the phases of the economic cycle. Moreover, Econometric tools such as Johansen’s cointegration test, the Vector error correction model and Impulse Response Functions are utilized. All determinant variables are found to be cointegrated and influence GDP growth and hence economic fluctuations. Results of this paper provide evidence that the fiscal policy rule seems to operate with various coefficients depending on the phase of the cycle. Keywords: Fiscal Policy; Band-Pass Filter; â€ŽCointegration; Jordan. JEL Classifications: E3, E62 DOI: https://doi.org/10.32479/irmm.7206